Database system architecture supporting coexisting query languages and data models - Hepp, Pedro E. (The University of Edinburgh, 1983)
Database technology is already recognised and increasingly used in administering and organising large bodies of data and as an aid in developing software. This thesis considers the applicability of this technology in small but potentially expanding application environments with users of varying levels of competence. A database system architecture with the following main characteristics is proposed: Database technology is already recognised and increasingly used in administering and organising large bodies of data and as an aid in developing software. This thesis considers the applicability of this technology in small but potentially expanding application environments with users of varying levels of competence. A database system architecture with the following main characteristics is proposed:Database technology is already recognised and increasingly used in administering and organising large bodies of data and as an aid in developing software. This thesis considers the applicability of this technology in small but potentially expanding application environments with users of varying levels of competence. A database system architecture with the following main characteristics is proposed : 1. It is based on a set of software components that facilitates the implementation and evolution of a software development environment centered on a database. 2. It enables the implementation of different user interfaces to provide adequate perceptions of the information content of the database according to the user's competence, familiarity with the system or the complexity of the processing requirements. 3. it is oriented toward databases that require moderate resources from the computer system to start an application. Personal or small-group databases are likely to benefit most from this approach.
Keywords: Database technology; software development; database system architecture